The impact of green supply chain management (GSCM) to sustainable performance: A study of critical success factors (CSFS) - Ng, Kai Lay; Abdullah, Rohani (2012)
The purpose of this paper is to briefly review the literature of the impact of Green Supply Chain Management (GSCM) to sustainable performance. Environmental issues constitute continuous concern for governments, societies, and business organizations. GSCM emerged as a new approach that extends environmental responsibility of organizations throughout their entire supply chains.The paper also discusses the Critical Success Factors (CSFs) for GSCM in term of green initiatives include regulation, the level of environmental commitment, customer and social requirement, supply network compliance, and company compliance by literature review on 15 articles.